The Relevance of deep ecological principles in Aquatic Crisis: A philosophical Analysis - Monday, Osebor Ikechukwu (Bangladesh Journal of Bioethics, 2020)
Ethics is a branch of philosophy that analyzes right or wrong of an action. Ethics studies all aspect of human activities; which water pollution is one. Water pollution is the emission of waste or chemicals into water bodies at a quantity that is harmful to man and the aquatic organisms. The Effects of water pollution include mass extinction species, decrease in the biodiversity, and scarcity of fresh water. The question to ask is “how can water pollution be ameliorated if not totally eradicated?” Using the method of philosophical analysis, the paper suggests that the implementation of deep ecological principles by policy makers would be abatements and environmental consciousness for the common good of the society.